A survey of the reactivity of in vitro diagnostic bilirubin reagents developed in Japan using artificially prepared bilirubin materials: A comparison of synthetic delta, unconjugated, and taurine-conjugated bilirubin. (November 2021) - Kiuchi, Sachiko; Ihara, Hiroshi; Osawa, Susumu; Ishibashi, Midori; Kinpara, Kiyoko; Ohtake, Kazuko; Ida, Takehisa; Miura, Yoshinori; Fujimura, Yoshiyuki; Ueda, Shigeru; Hirano, Yuuki; Watahiki, Kensuke; et al.
Background: In vitro diagnostic bilirubin reagents based on oxidation with bilirubin oxidase or vanadic acid for total and direct-reacting bilirubin are widely used in Japan; however, their reactivity to unconjugated and conjugated bilirubin and delta bilirubin has not been completely disclosed by manufacturers. We used artificially prepared bilirubin materials to investigate the reactivity with four in vitro diagnostic bilirubin reagents. Methods: Porcine unconjugated bilirubin solution, chemically synthesized ditaurobilirubin solution, and chemically synthesized delta bilirubin solution were used as surrogates of naturally occurring unconjugated bilirubin, conjugated bilirubin, and delta bilirubin, respectively. The total bilirubin and direct-reacting bilirubin concentrations were measured by three bilirubin oxidase methods and one vanadic acid method, and the observed concentrations were compared with those obtained by the diazo-based reference measurement procedure. Results: The unconjugated bilirubin and delta bilirubin concentrations were similar when any of the four in vitro diagnostic bilirubin reagents were used during total bilirubin measurement. This was consistent with reference measurement procedure and exhibited a converged inter-method variation. Compared with reference measurement procedure, significantly low ditaurobilirubin concentrations were observed by the in vitro diagnostic bilirubin reagents despite the converged inter-method variation. In delta bilirubin measurement, some reagents reacted doubtfully with unconjugated bilirubin, while showed lower ditaurobilirubin concentrations than its corresponding total bilirubin concentration. Reactivity with delta bilirubin was different for each method including reference measurement procedure. Some reagents were developed to react less with delta bilirubin and others to strongly react with delta bilirubin. Conclusions: We revealed the reactivity of IVD-TB and IVD-DB reagents to artificially prepared bilirubin materials, and their consistency with reference measurement procedure. The delta bilirubin data results vary depending on the reagents used.